Enhancing Students' Self-Confidence via Guided Inquiry and Information Services Intervention - Faris Abdurrahman; Neviyarni Suhaili; Firman Firman; Dina Sukma (Journal of Educational, Health and Community Psychology, 2024)
This study employed a randomized experiment with a control group design and utilized a validated and reliable questionnaire for data collection. It investigates the efficacy of information services employing an inquiry model compared to those without special treatment in enhancing students' self-confidence. The sample comprised 58 students from a State Junior High School in Padang. Data analysis involved t-tests and statistical tests utilizing n-gain scores, with the research instrument employing a Likert scale model. The findings indicate that information services utilizing the guided inquiry model are more effective in enhancing students' self-confidence. Further discussion was explained in the article.